(untitled) (Philological Studies, 2019)
The paper focuses on the Macedonian sacred sites identified as “fairy”, and their transformation over time, both in terms of their spatial changes, and embedded cultural values. It is based on data conducted through my own field research, during 2014 in places: Samovilska voda (Fairy water), in Zubovce, near Kumanovo and Lekovita voda/crkva Sv. Kuzman i Damjan (Healing water/Church St. Kuzman and Damjan) in the village of Govrlevo, near Skopje. The paper aims to show how the narratives, beliefs and practices, related to these places, evolved and developed over time, by taking the value of the Christian tradition.